Shedding Light on the Diverse Reactivity of NacNacAl with N‐Heterocycles. Issue 37 (25th June 2020) - Dmitrienko, Anton; Pilkington, Melanie; Britten, James F.; Gabidullin, Bulat M.; van der Est, Art; Nikonov, Georgii I.
Abstract: The aluminum(I) compound NacNacAl (NacNac=[ArNC(Me)CHC(Me)NAr] −, Ar=2, 6‐ i Pr2 C6 H3, 1 ) shows diverse and substrate‐controlled reactivity in reactions with N‐heterocycles. 4‐Dimethylaminopyridine (DMAP), a basic substrate in which the 4‐position is blocked, induces rearrangement of NacNacAl by shifting a hydrogen atom from the methyl group of the NacNac backbone to the aluminum center. In contrast, C−H activation of the methyl group of 4‐picoline takes place to produce a species with a reactive terminal methylene. Reaction of 1 with 3, 5‐lutidine results in the first example of an uncatalyzed, room‐temperature cleavage of an sp 2 C−H bond (in the 4‐position) by an Al I species. Another reactivity mode was observed for quinoline, which undergoes 2, 2′‐coupling. Finally, the reaction of 1 with phthalazine produces the product of N−N bond cleavage. Abstract : Reactivity pathways of NacNacAl with various N‐heterocycles have been investigated and diverse and highly substrate‐controlled reactivity patterns have been discovered. Cases of unusual sp 3 and sp 2 C−H bond activation, C−C coupling, and N−N bond cleavage are reported. NacNac=[ArNC(Me)CHC(Me)NAr] −, Ar=2, 6‐ i Pr2 C6 H3 .